Asean dan Pembangunan Ekonomi Maritim Kepulauan Riau – Indonesia - Akhirman Akhirman (Program Studi Manajemen Fakultas Ekonomi UMRAH, 2018)
This study aims to find out the Maritime Economic Development of ASEAN Countries and Riau Islands - Indonesia. ASEAN which was established on August 8, 1967 through the Bangkok Declaration by Indonesia, the Philippines, Malaysia, Singapore, and Thailand. Then in 1984 he joined the State of Brunei Darussalam, in 1995 followed by the country of Vietnam, in 1997 the countries of Laos and Myanmar, and in 1998 joined the country of Cambodia. ASEAN in the Indonesian language known as Perbara or Perhimpunan Nations of Southeast Asia is a collaborative organization in the field of economy and geo-politics. The variables used in this study are Economic Growth, Export Rate. Inflation, and IPM. The data used is time series data, namely from 2014-2016. The analytical method used in this study is descriptive and econometric analysis. World Bank data, in 2017, predicts that there are three countries, namely Cambodia, Laos and Myanmar, which are predicted to have the most expansive economic growth after India in 2017-2019, and it is estimated that economic growth can reach 7%. while Indonesia in Quarter II 2017 grew 5.1 percent (BPS, 2017), while in 2013 it grew 5.58 percent. Riau Islands, a small town that captures part of NKRI in 2015 6.02 percent (yoy) economic growth, in the second quarter of 2017 must be willing with the lowest number two national economic growth, which is 2.02 percent which was the highest in Sumatra exceed national figures of 4.79 percent. (yoy). Suggestions given in this study include the need to think about a policy strategy that has potential economic areas to support sustainable export growth so that it can improve economic growth better.